Academic Library Services during Post-Covid Era: A Case Study - Oak, Meenal; Nasiruddin, Md (The National University Journal of Humanities, Social Sciences and Business Studies, 2023)
Libraries and Information centres, from the last so many decades serve as a strong resource of information to the society. The libraries as academic institutions are considered as a heart of the parent organizations and the role is played in the current era very well by providing the online as well as print information resources to the clientele. During the last year, due to Covid 19 pandemic effect, the entire academic world has been badly affected and changed the global education scenario. It has changed the way of processes and delivery of education; being a part of the education system, academic libraries are also not exceptional for that. Academic libraries are also witnessing a sea change in the storage, processing and service delivery of information. Academic libraries will have to redesign, reform the nature of library collection, processes and also the service delivery of information in order to exceed the user expectations and remain sustainable in the present scenario of the Post Covid-19 era. Thus, the present work has highlighted an effort of a management Institutional library taken to reshape, reform and reorganize the library services and collection in order to meet the new challenges for sustainability. NU Journal of Humanities, Social Sciences & Business Studies Vol. 7 & 8, No.2 & 1, July 2021 - December 2022 p. 99-110